2021
DOI: 10.2174/1389450121999201125200132
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Resistance Protein: A Potential Therapeutic Target for Cancer

Abstract: : Breast Cancer Resistance Protein (BCRP) is an efflux transporter responsible for causing multidrug re-sistance(MDR). It is known to expel many potent antineoplastic drugs, owing to its efflux function. Efflux of chemothera-peutics because of BCRP develops resistance to manydrugs, leading to failure in cancer treatment. BCRP plays an important role in physiology by protecting the organism from xenobiotics and other toxins. It is a half-transporter affiliated to theATP-binding cassette (ABC) superfamily of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Its overexpression may contribute to intrinsic drug resistance in vitro. BCRP/ABCG2 expression can be found in the brain, liver, and lung cancers and acute myeloid leukemia [6]. Research has found BCRP/ABCG2 is typically expressed in the ducts and lobules of mammary tissue [7].…”
Section: Introductionmentioning
confidence: 99%
“…Its overexpression may contribute to intrinsic drug resistance in vitro. BCRP/ABCG2 expression can be found in the brain, liver, and lung cancers and acute myeloid leukemia [6]. Research has found BCRP/ABCG2 is typically expressed in the ducts and lobules of mammary tissue [7].…”
Section: Introductionmentioning
confidence: 99%